Application of Theory of Queues via Computational Modeling in a Vehicle Wash Company (Research, Society and Development, 2021)
Currently, queuing has been recurrent for resource allocation, especially when considering several growing urbanization scenarios, since such events encourage the queues formation that are directly related to the population density, which increases competition for resources. In this context, there are several configurations of queues in sectors that are indispensable for the population, becoming essential to manage processes that involve queues. Therefore, this work aims to investigate tools for reducing service capacity in companies of the vehicle washing sector, aimed to avoid queues formation, which generally represent damage to customers and even companies. This investigation focuses on the Theory of Queues, the Theory of Constraints and Computational Modeling. The main objective of this research is to show a powerful tool for organizing and optimizing processes that involve queues.